2019
DOI: 10.1186/s41074-019-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermal non-line-of-sight imaging from specular and diffuse reflections

Abstract: This paper presents a non-line-of-sight technique to estimate the position and temperature of an occluded object from a camera via reflection on a wall. Because objects with heat emit far infrared light with respect to their temperature, positions and temperatures are estimated from reflections on a wall. A key idea is that light paths from a hidden object to the camera depend on the position of the hidden object. The position of the object is recovered from the angular distribution of specular and diffuse ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Using specular reflections requires directly sampling the path from the hidden scene to the relay surface, needing strong assumptions about surface albedo and orientation [Lindell et al 2019a], or placing the scanning system far from the relay surface [Scheiner et al 2020]. Specular reflections produced by infrared wavelenghts have also been utilized for passive NLOS [Kaga et al 2019;Maeda et al 2019b]. These systems are also restricted to reconstructions of planar scenes or to object tracking inside the hidden scene.…”
Section: Related Workmentioning
confidence: 99%
“…Using specular reflections requires directly sampling the path from the hidden scene to the relay surface, needing strong assumptions about surface albedo and orientation [Lindell et al 2019a], or placing the scanning system far from the relay surface [Scheiner et al 2020]. Specular reflections produced by infrared wavelenghts have also been utilized for passive NLOS [Kaga et al 2019;Maeda et al 2019b]. These systems are also restricted to reconstructions of planar scenes or to object tracking inside the hidden scene.…”
Section: Related Workmentioning
confidence: 99%
“…However, the performance of these methods is often compromised by the significant scattering produced by the rough surface of the wall and the visible ambient light. We and several authors have reported that the use of long-wave-infrared (LWIR) light has several advantages that can reduce these difficulties [16,[17][18][19][20]. First, thermally-elevated objects such as human subjects are seen as light emitters, and these signals stand out amongst the ambient background.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, various principles have been explored for NLOS imaging, including speckle correlations [4,5], transient imaging [6,7], photon counting imaging [8,9] and intensity imaging [10,11]. Most existing methods exploited how to identify the NLOS scene by using time-of-flight (TOF) of photons information from the backscattered signal [12,13].…”
Section: Introductionmentioning
confidence: 99%